Pengaruh Non Performing Loan (NPL), Capital Adequancy Ratio (CAR) Dan Net Interest Margin (NIM) Terhadap Harga Saham Pada Bank BUMN - Fransiska Saputri Desy; Nafisah Nurulrahmatiah; Puji Muniarty (Indo Publishing, 2025)
The purpose of this study is to analyze the effect of Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) on stock prices in State-Owned Banks. The type of research used is associative. The instrument used in this study is a list of tables in the form of financial reports consisting of balance sheet and income statement data in the form of non-performing loan data, total credit, total equity, RWA, interest income, productive assets and stock prices for 5 years, namely from 2019 to 2023. The population in this study is all state-owned banks listed on the IDX from 2019-2023, namely 5 banks. The sample in this study is 4 state-owned banks listed on the IDX from 2019-2023. With the sampling technique used is purposive sampling. Data collection techniques used in this study are documentation techniques and literature studies. The data analysis techniques used are classical assumption tests, multiple linear regression analysis, multiple correlation coefficients, determination tests, t tests and f tests. The results of the study show that Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) have a significant simultaneous effect on Stock Prices in state-owned banks.